Factors associated with the seroprevalence of Toxoplasma gondii in pigs from technologically advanced and nontechnical farms in Lima, Peru - Luyo A., Christian (2017)
The aim of this study was to determine the seroprevalence of Toxoplasma gondii in pigs from technologically advanced and nontechnical farms in Lima, Peru and to identify factors associated with the transmission. Epidemiological surveys were applied on farms to identify potential factors associated with the transmission of T. gondii in pigs. Blood samples were collected in the slaughterhouse from pigs in the finishing phase: 264 from technologically advanced farms and 143 from nontechnical farms. Serum samples were analyzed for the diagnosis of swine toxoplasmosis by the indirect ELISA technique. The association between seroprevalence of T. gondii and variables sex, origin, animal density, water source, housing, presence of cats and rodent control were analyzed using multiple models of logistic regression. The seroprevalence of T. gondii in pigs from technologically advanced and nontechnical farms was 4.5 and 33.6% respectively. Factors associated with the transmission of T. gondii in pigs were the origin (OR: 10.61), water source (OR: 6.44), type of housing [mixed (OR: 6.14) and free range (OR: 13.59)], presence of felines [1- 3 (OR: 5.29) and >3 (OR: 16.02)], and rodent control (OR: 7.81).